Scientific Whispers: Mapping Innovative Pedagogies in STEAM and Programming Education - Antunes, M.; Trigo, A. (5th International Computer Programming Education Conference (ICPEC 2024), 2024)
Traditional education, especially in STEAM and programming, faces several challenges in capturing the attention and stimulating the new student generation. These challenges are exacerbated by rigid teaching methods and reflect a global difficulty in the educational sector, primarily stemming from the disconnect between traditional teaching and the contemporary needs of the modern world. This article presents a systematic literature review with a mapping study to explore innovative approaches currently employed in teaching, specifically focusing on STEAM and programming education. The conclusions reached make a significant contribution to the field of education, and the mapping conducted has identified the teaching methodologies most researched and investigated by the scientific community. This research also presents a classifying proposal for those methodologies, considering their characteristics and weighing up three dimensions: resources, implementation and receptiveness. As a final reflection, some emerging methodologies were identified that are believed to have great potential to be used for STEAM and programming education.